(untitled) (International Journal of Engineering and Computer Science, 2023)
E-learning allows to share and manage knowledge and skills of the professionals and to get the right information to the right people whenever they need it. E-learning is defined as pedagogy empowered by digital technology which involves learning done at a computer, usually connected to a network, giving us the opportunity to learn almost anytime, anywhere. There are many software systems available that provide distance learning environment. This software is in both forms, commercial and open source software (OSS). Blackboard is one of the Open source tool that have been increasingly gaining worldwide popularity in e-learning system. This paper is highlights the significance of open source tools in online education system. The popularity of open source tools day by day increases. A huge number of Students are linked and gaining degree in feasible mode.